OUTCOMES AFTER PARS PLANA VITRECTOMY FOR EPIRETINAL MEMBRANES ASSOCIATED WITH TOXOPLASMOSIS. Issue 9 (September 2016) - Miranda, Ana F.; Costa de Andrade, Gabriel; Novais, Eduardo A.; Maia, André; Nascimento, Heloisa; Muccioli, Cristina; Belfort, Rubens
Abstract : Purpose: To evaluate outcomes and complications of pars plana vitrectomy in patients with epiretinal membrane secondary to toxoplasmic retinochoroiditis. Methods: Retrospective evaluation of the records of 14 patients who underwent pars plana vitrectomy for epiretinal membrane secondary to toxoplasmic retinochoroiditis. The best-corrected visual acuity, intraoperative and postoperative complications, and macular optical coherence tomography were analysed. All patients received postoperative prophylactic treatment with trimethoprim/sulfamethoxazole. Results: Fourteen patients, 5 men and 9 women, were included. Mean follow-up period after surgery was 6.07 ± 2.64 months. Preoperative mean best-corrected visual acuity was 20/200, and postoperative mean best-corrected visual acuity was 20/60. There were no intraoperative complications. Three patients developed posterior capsule opacification, and one patient developed cataract. Conclusion: Pars plana vitrectomy is a safe and effective procedure in patients with epiretinal membrane secondary to toxoplasmic retinochoroiditis, improving both visual acuity and anatomical result on macular optical coherence tomography. The most frequent postoperative complications were posterior capsule opacification and cataract. No recurrences of the disease were recorded. Abstract : Epiretinal membrane formation is a complication of ocular toxoplasmosis, causing reduced visual acuity. In this study, surgery followed by postoperative prophylactic treatment with trimethoprim/sulfamethoxazole resulted in improved visual acuity in most patients. Posterior capsule opacification and cataract were the most frequent postoperative complications, and no reactivations were recorded.